1997
DOI: 10.1111/j.1467-6494.1997.tb00958.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult Attachment Styles, the Desire to Have Children, and Working Models of Parenthood

Abstract: College students who had yet to marry and begin a family were asked about their desire to have children and their beliefs and expectations about themselves as parents (Study 1) and the characteristics of their prospective children (Study 2). Persons with more avoidant and anxious-ambivalent models of close adult relationships harbored more negative models of parenthood and parent-child relationships. These findings indicate that working models of parenting and parent-child relationships form well before marria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
148
0
13

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(186 citation statements)
references
References 52 publications
20
148
0
13
Order By: Relevance
“…[84] people were concerned about their capacity to be a good parent, but their attachment style was unrelated to their desire for children. A later study found that avoidantly attached people believed that their children would exhibit negative/ insecure behaviour [101], while anxious-ambivalently attached people did not expect this. The authors speculate that, in line with Belsky [84], avoidantly attached people still have children despite low desire due to social norms, but offer lower parental investment.…”
Section: (E) Attachment Stylementioning
confidence: 99%
“…[84] people were concerned about their capacity to be a good parent, but their attachment style was unrelated to their desire for children. A later study found that avoidantly attached people believed that their children would exhibit negative/ insecure behaviour [101], while anxious-ambivalently attached people did not expect this. The authors speculate that, in line with Belsky [84], avoidantly attached people still have children despite low desire due to social norms, but offer lower parental investment.…”
Section: (E) Attachment Stylementioning
confidence: 99%
“…Alguns deles têm demonstrado que os indivíduos inseguros, especialmente os evitantes, tendem a revelar níveis menores de proximidade aos filhos e a fornecer-lhes menos suporte (Rholes, Simpson, & Blakely, 1995). Cumulativamente, apresentam modelos internos da parentalidade mais negativos do que os indivíduos seguros (Rholes, Blakely, Simpson, Lanigan, & Allen, 1997). A perceção da qualidade da relação com o(a) parceiro(a) parece, no entanto, influenciar este resultado.…”
Section: Vinculação Interface Trabalho-família E Parentalidadeunclassified
“…İlk bağ büyük olası-lıkla anneye karşı oluşur, daha sonra buna başka özel insanlar da eklenir. 1 Bağlanma teorisi, bebeğin ihtiyaçları için sinyal göndermesi ile bakım veren eriş-kinin buna uygun cevabı sonucu güvenli bebekebeveyn bağlanması oluşması esasına dayanır. 2 Bebeklik döneminde duygusal gelişimin sağlıklı olabilmesinde anahtar rolü anne-baba oynamaktadır.…”
Section: Baba-bebek Bağlanması Veunclassified